Biochemical and molecular aspects of dimorphism in fungi - Pathan, Ejaj K.; Ghormade, Vandana; Panmei, Redeemson; Deshpande, Mukund V. (Advancing Frontiers in Mycology & Mycotechnology, 2019)
Most of the eukaryotic differentiation processes are unidirectional. However, fungi have the ability to grow reversibly as unicellular yeast (Y) or as filamentous hypha (H) in response to the specific strain-dependent environmental stimuli. Such a phenomenon known as “dimorphism” is not limited to a specific class of fungi. Most of the plant, human, and insect pathogenic fungi show Y-H and reversible morphogenesis, associated with their saprophytic to pathogenic change, for survival and proliferation in the host. In this chapter, we have described the factors stimulating dimorphism, the signal transduction pathways induced by these stimuli, changes in the gene/protein expression patterns due to a cascade of these signals, and, finally, translation of this genotypic effect into phenotypic change, i.e., the morphological outcome. The process of fungal differentiation and formation of tumor cells follow the same regulatory series of events, involving cAMP, MAP, and RAS kinase cascades. Therefore, the molecules inhibiting Y-H transition in fungi can be explored for their anticancer potential.